POLITIK HUKUM KEBIJAKAN KANTONG PLASTIK BERBAYAR - Hidayat, Nur Azizah (Al-Qisth Law Review, 2017)
SE MKLH Number: SE-06 / PLB3-PS / 2015 and SE MKLH Number: S.1230 / PBL3-PS / 2016, is a Circular Letter of the Ministry of Environment and Forestry Directorate General of Waste Management, Waste and Hazardous and Toxic Materials, containing applying the application of paid plastic bags (PPB) to modern retail business. The appeal through the two Circular Letters is done because Indonesia has been ranked second in the use of environmental polluter bags after China. This paper aims to examine (1). political laws of PPB policy from a political, sociological, economic and philosophical perspective; (2). purpose of political content of KPB policy law; and (3). law enforcement policy of PPB. The conclusion of this study is that PPB policy is needed to change the behavior of highly consumptive society and change the paradigm of waste management, so that what is aspired in Article 5 paragraph (1), Article 20, Article 28H paragraph (1), and Article 33 paragraph (3) and paragraph (4) of the 1945 Constitution of the State of the Republic of Indonesia can be realized through Law Number 18 Year 2008, Government Regulation Number 81 Year 2012 and MKLH Regulation concerning CDE policy to be designed.